2015
DOI: 10.1021/jacs.5b04471
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Dynamics of the Troponin I C-Terminal Domain: Combining Single-Molecule and Computational Approaches for a Disordered Protein Region

Abstract: In recent years, single-molecule Förster resonance energy transfer (smFRET) has emerged as a critical and flexible tool in structural biology, particularly in the study of highly dynamic regions and molecular assemblies. The usefulness of smFRET can be further extended by combining it with computational approaches, marrying the coarse-grained experimental data with higher-resolution in silico calculations. Here we use smFRET to determine six pairwise distances within the intrinsically disordered C-terminal dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 36 publications
(90 reference statements)
2
70
0
Order By: Relevance
“…19; 49 However, this structure was immediately controversial, 16; 18; 50 and even its own authors noted that they were surprised at the number of salt bridges between their structure and its putative actin binding site given the known low affinity between them. 49 More recent work has indicated that TnI C is disordered in the open state, 16; 18; 50; 51 which calls the NMR structure into question. While the structure could still prove to be relevant to understanding the blocked state conformation, the thin filament was not included in experimental measurements and thus its potential to be a blocked state conformation is unclear.…”
Section: Tnic Dominates Transitions To and From The Open Statementioning
confidence: 99%
See 4 more Smart Citations
“…19; 49 However, this structure was immediately controversial, 16; 18; 50 and even its own authors noted that they were surprised at the number of salt bridges between their structure and its putative actin binding site given the known low affinity between them. 49 More recent work has indicated that TnI C is disordered in the open state, 16; 18; 50; 51 which calls the NMR structure into question. While the structure could still prove to be relevant to understanding the blocked state conformation, the thin filament was not included in experimental measurements and thus its potential to be a blocked state conformation is unclear.…”
Section: Tnic Dominates Transitions To and From The Open Statementioning
confidence: 99%
“…18; 19; 22; 23; 37; 50; 53 The separate structural models were recently established as one conformational ensemble using an integrated single-molecule fluorescence and simulation approach, which showed that the published models represent clusters of conformers favored in the disordered state (Figure 3, bottom panel). 51 The conformational ensemble was clustered by mapping 3.5 Å contacts, which highlights helices as strong contacts along the i,i+3 diagonal. The helical propensities clustered by the contact maps match the helical propensities in published structures: a single N-terminal helix in Cluster 1 matching the 1J1E structure, 23 two short helices in areas highlighted in the 1VDJ structure, 19 and a single C-terminal helix similar to that proposed by NMR and crystallography.…”
Section: Tnic Dominates Transitions To and From The Open Statementioning
confidence: 99%
See 3 more Smart Citations